1992
DOI: 10.1095/biolreprod47.2.162
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral Ovariectomy Increases Loss of Primordial Follicles and is Associated with Increased Metestrous Concentration of Follicle-Stimulating Hormone in Old Rats1

Abstract: The primary objective of these studies was to determine whether unilateral ovariectomy (ULO) would affect rate of loss of primordial follicles. In experiment 1, retired breeder rats, unilaterally ovariectomized and maintained on the experiment for 90 days after surgery, had fewer (p less than 0.01) primordial follicles per ovary than sham-operated controls of the same age. The purpose of experiment 2 was to determine whether time after ULO or age of rats was the critical factor necessary for increased loss of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
2
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(13 citation statements)
references
References 24 publications
0
10
2
1
Order By: Relevance
“…In support of this, we have found that while the expression of BMPRIB was detectable in follicular cells of mouse primordial follicles, FSHR was absent but later appeared in primary follicles. These data together with a previous report in rat (Moore & Shimasaki 2005) contradict previous reports (Meredith et al 1992, Flaws et al 1997 and therefore suggest the presence of a complex interplay between gonadotrophins and other growth factors such as BMPs where direct and indirect cross-signalling regulates ovarian function (Tanwar & McFarlane 2011). The reported decrease in primordial follicles after eCG treatment (Tanwar et al 2008) conflicts with the present result probably due to the manual counting method used in the previous study instead of the automated stereology used in this work.…”
Section: The Role Of Bmps In Ovarian Functioncontrasting
confidence: 96%
See 1 more Smart Citation
“…In support of this, we have found that while the expression of BMPRIB was detectable in follicular cells of mouse primordial follicles, FSHR was absent but later appeared in primary follicles. These data together with a previous report in rat (Moore & Shimasaki 2005) contradict previous reports (Meredith et al 1992, Flaws et al 1997 and therefore suggest the presence of a complex interplay between gonadotrophins and other growth factors such as BMPs where direct and indirect cross-signalling regulates ovarian function (Tanwar & McFarlane 2011). The reported decrease in primordial follicles after eCG treatment (Tanwar et al 2008) conflicts with the present result probably due to the manual counting method used in the previous study instead of the automated stereology used in this work.…”
Section: The Role Of Bmps In Ovarian Functioncontrasting
confidence: 96%
“…Specifically, it has been commonly believed that FSH may be involved in the initial recruitment of primordial follicles (Meredith et al 1992, Flaws et al 1997. However, recent observations have demonstrated that these follicles develop normally in mice lacking active FSH or FSH receptor (FSHR) due to gene mutation in FSH b subunit (Siegel et al 2013) or FSHR (Dierich et al 1998), suggesting that initial follicle recruitment is gonadotrophin independent (Orisaka et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…There is very little evidence to suggest that unilateral oophorectomy by itself has any major impact on the natural age related decline in fertility and on the time of menopause. Women with a single ovary may have slightly elevated serum FSH concentrations (Cooper and Thorp, 1999) and animal studies have shown increased serum FSH concentrations and numbers of antral follicles in the remaining ovary but decreased total number of antral follicles per animal, compensatory hypertrophy in the remaining ovary and menstrual irregularity after unilateral oophorectomy (Butcher, 1985;Martin et al, 1986;Meredith et al, 1992). However, women with one ovary appear to have an unreduced fertility potential, be it naturally or via IVF (Lass, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, unilateral oophorectomy increases the loss of remaining primordial follicles in middle-aged rats but not in young rats operated on at 30 days of age (158). Likewise, treatment with a chemotherapy agent, busulfan, decreases the resting follicle pool by more than 90% in rats and substantially accelerates follicle depletion (159).…”
Section: B Do Women Of Reproductive Age Who Have Undergone Unilateramentioning
confidence: 96%